Analisis Kepuasan Pengguna terhadap Aplikasi M-Paspor dalam Perspektif Implementasi E-Government di Indonesia - Oktavia Anggi Ramadhani; Khansa Nabilla Lutfiyah; Devita Larasati Tupen; Fadhia Chalisha Adzzahra; Fatkhuri (Penerbit Jurnal Indonesia, 2025)
This study aims to analyze the level of user satisfaction with the M-Paspor application and assess the factors that influence it in the context of e-government implementation in Indonesia. This study uses a descriptive qualitative approach, with data collection through literature studies, secondary data, and analysis of user reviews on Google Play Store from January to March 2025. The analysis was conducted using a thematic approach based on the IS Success Model theory, which consists of six dimensions: system quality, information quality, service quality, usage, user satisfaction, and individual impact. The results of this study indicate that the M-Paspor application is capable of improving the efficiency of digital passport application services and significantly reducing queues at immigration offices. Features such as digital document uploads, online queue scheduling, and automatic app notifications are considered to provide convenience and speed up the service process. However, various technical challenges were also identified, such as system errors, slow app response times, and difficulties accessing features, which remain the primary complaints of users. Additionally, the app's non-intuitive navigation and the need for repeated data entry also impact user satisfaction, particularly among those less familiar with technology. This study indicates that the success of e-government through the M-Paspor app is not solely determined by technological sophistication but also by service responsiveness, ease of access, and public acceptance and satisfaction with government digital innovations. These findings are expected to contribute practically to the development of more efficient, transparent, and user-satisfaction-oriented digital public services